Russia Economic Report, No. 36, November 2016 : The Russian Economy Inches Forward - Will that Suffice to Turn the Tide? - World Bank Group (World Bank, Washington, DC, 2016)
Global growth is weak. It slowed down to 2.2 percent in the first half of 2016. While the Brexit vote has had a limited impact on global growth so far, growth in advanced economies (AE) has been disappointing. Amidst external headwinds, the recession continues in Russia, although the pace of gross domestic product (GDP) decline has slowed down. After a prolonged recessionary period, headline economic and financial trends and indicators are now picking up. Fiscal tightening at the federal level may also adversely affect the performance of some regions. For 2016, the authors project growth of the Russian economy at -0.6 percent, an improvement from earlier June forecast of -1.2 percent. This growth upsurge, however, is unlikely to turn the tide in terms of building a more diversified economy. While a detailed analyses of structural issues is beyond the scope, bolstering investor sentiment towards Russia by reducing policy uncertainty will help. One important step forward, particularly in light of eroding fiscal buffers with the reserve fund expected to be depleted in 2017, is a return of the medium-term fiscal framework.